Faktor-Faktor Efektif dalam Pengelolaan Jaringan Irigasi Kewenangan Pusat di Provinsi Jawa Barat - Achmad Rizal; FX Hermawan Kusumartono; Nanang Rianto (Balai Teknik Irigasi, 2018)
The success of operation and maintenance of irrigation network was influenced by the performance of irrigation network management institution. This aspect becomes an additional burden of achievement of irrigation network management. The objective of this study was to find factors that influence the effectiveness of irrigation system management. This study used descriptive methods based on a fishbone scheme and a multi-variable regression. Fishbone diagram used to find the root of problem on irrigation management. Important factors discovered with fishbone technique then continued with multi-variable regression to emphasize to what extent do those factors influence the irrigation management. Independent variables use were physical infrastructure, plant productivity, supporting tools, organization of personnel, documentation, and organization condition. Data were collected primary and secondary from institution also government officials and farmers who were members of water user association (P3A). The results showed that significant factors which influence in improving the effectiveness of irrigation system management were physical infrastructure, personnel organization and supporting facilities. In the future, theres an urgency to develop systems which can measure management capacity changes related to operation and maintenance from time to time.